Respuesta :
Answer: a) 10x-6x and c) 12x+2x-10x
Step-by-step explanation:
Lets start by simplifying all the expressions
a) 10x-6x=4x
b)7x+3x=10x
c)12x+2x-10x=14x-10x=4x
d)x-x+2x=2x
As you can see a and c both simplify to 4x meaning that is our answer.
Answer:
Options A and C
Solution:
- In order to simplify these expressions, we should combine like terms:
- 10x-6x=4x
- 7x+3x=10x
- 12x+2x-10x=14x-10x=4x (so expressions A & C are equivalent)
- x-x+2x=0x+2x=2x
Hope it helps.
Do comment if you have any query.